Quality of life in people with cognitive impairment: nursing homes versus home care. (May 2015) - Nikmat, Azlina Wati; Al-Mashoor, S. Hassan; Hashim, Nurul Azreen
ABSTRACT Background: The evaluation of quality of life (QoL) among older adults has become increasingly important, and living arrangements play a pivotal role in determining the QoL of people with cognitive impairment (PWCI). Although informal care (home-based) is favored, transition to formal care (residential care) often becomes necessary, especially in the later stages of cognitive impairment. The primary objective was to compare the QoL of PWCI in the community and nursing homes. Additionally, factors differentiate the QoL of PWCI in these two settings were identified. Methods: This is a quasi-experimental study design involving 219 older adults with cognitive impairment, aged 60–89 years old from both nursing home and home care. Participants completed the EUROPE Health Interview Survey-QoL (WHO-8), the Short Mini-Mental State Examination (SMMSE), the Barthel Index (BI), the Geriatric Depression Scale (GDS-15), and the Friendship Scale (FS). Results: There were significant differences in QoL, depression, social connectedness (p < 0.01) and cognitive functions (p = 0.01) between home care recipients and nursing home participants. No significant differences were observed with regards to health condition, co morbidities and physical functions between study cohorts. Conclusions: Older adults with cognitive impairment living at home experienced higher QoL, had better cognitive function, were less depressed and reported higher social connectedness compared to those living in institutional care. Therefore, support should be provided in enabling home care and empowering caregivers to provide better care for PWCI.